Tackling the increasing complexity of CF care. (3rd September 2015) - Sawicki, Gregory S.; Goss, Christopher H.
Summary: Health outcomes for individuals with cystic fibrosis (CF) have dramatically improved in parallel with better organization of clinical care systems, evolution of novel therapeutics, and improvements in diagnosis and screening for CF and CF‐related complications. In parallel with these advances has come an increasing complexity and burden of care, leading to challenges with adherence to treatment regimens. As novel therapeutics continue to be developed and introduced to the CF care regimen, there are clear opportunities to refine and personalize care. This can be done by adding comparative effectiveness research to the CF clinical research paradigm and integrating novel technologies in drug delivery and remote monitoring that can facilitate adherence but also reduce the burden of treatment while maintaining efficacy. This review highlights both the challenges of the increasingly complex treatment regimens in CF and the opportunities to advance care by addressing adherence, implementation science, comparative effectiveness, and integration of novel technologies in CF care.Pediatr Pulmonol. 2015; 50:S74–S79. © 2015 Wiley Periodicals, Inc.